2018
DOI: 10.1111/jvh.13018
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the decline and future of hepatitis A transmission in Australia

Abstract: Summary Hepatitis A incidence has declined in most countries through a combination of prevention measures, augmented through the use of a highly effective vaccine. In Australia, the proportion of the population susceptible to hepatitis A infection has declined over time due to high rates of opportunistic vaccination as well as the sustained inflow of seropositive immigrants from high‐endemicity countries. These factors have contributed to a rapid decline in incidence. An age‐structured hepatitis A transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…for more than one generation. [177][178][179] Using a disease transmission dynamic modeling approach, the impact of universal versus regional vaccination on hepatitis A morbidity and the cost-effectiveness was projected for up to 100 years for the US: universal vaccination was cost-saving compared with regional vaccination policy; in addition, herd protection effects of the hepatitis A vaccination programs had a significant impact on mortality, morbidity, and cost-effectiveness ratios. 177 Based on Mexican data, the potential impact of HAV vaccine immune memory on the modeled reduction of hepatitis A disease in vaccinated subjects was explored for time periods of up to 75 years: the analysis indicated that routine vaccination of toddlers against hepatitis A virus would be cost-effective in Mexico using a single-dose strategy.…”
Section: Effect Of Universal Mass Vaccination (Umv) On Disease Burdenmentioning
confidence: 99%
See 1 more Smart Citation
“…for more than one generation. [177][178][179] Using a disease transmission dynamic modeling approach, the impact of universal versus regional vaccination on hepatitis A morbidity and the cost-effectiveness was projected for up to 100 years for the US: universal vaccination was cost-saving compared with regional vaccination policy; in addition, herd protection effects of the hepatitis A vaccination programs had a significant impact on mortality, morbidity, and cost-effectiveness ratios. 177 Based on Mexican data, the potential impact of HAV vaccine immune memory on the modeled reduction of hepatitis A disease in vaccinated subjects was explored for time periods of up to 75 years: the analysis indicated that routine vaccination of toddlers against hepatitis A virus would be cost-effective in Mexico using a single-dose strategy.…”
Section: Effect Of Universal Mass Vaccination (Umv) On Disease Burdenmentioning
confidence: 99%
“…178 With an age-structured hepatitis A transmission model, incorporating demographic changes and fitted to seroprevalence and disease notification data, the decline and future of hepatitis A transmission in Australia was projected for the following 40-50 years: the results suggest that sustained endemic transmission in the general Australian population is no longer possible although risks of sporadic outbreaks remain. 179 For such projections not only vaccination coverage and long-term immunogenicity has to be taken into account, but also the vaccine-induced immune memory 178 (section 3.2), the herd protection effect 177,180 (section 4.2), and the transmission mode, 179 as well as the shifting of HAV epidemiology, clean water access and hygiene standards. 13 The WHO advises to regularly assess the impact of hepatitis A UMV's, using information on morbidity and mortality generated by surveillance and study data; in addition, duration of immune protection by 1-and 2-dose schedules should be monitored.…”
Section: Effect Of Universal Mass Vaccination (Umv) On Disease Burdenmentioning
confidence: 99%
“…Since 2012, MSHC has had an in-house free vaccination programme targeting MSM aged under 20 years, who only had 19% immunity reported as of 2011 11. However, the lower proportion of MSM aged under 30 years who are immune remains substantially less than is required to prevent sporadic outbreaks 14 22. Clearly, continued efforts are required to ensure that younger MSM receive the hepatitis A vaccine to increase herd immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Mathematical modelling has provided a suggested vaccination threshold for the potential elimination of hepatitis A infection within Australia, assuming modest vaccine coverage 22. However, among high-risk groups, sporadic outbreaks may continue to contribute to notifications if seroprevalence of hepatitis A remains below 70% 14 22.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation